Review of multilevel current source inverters of wind power stations - Aleksey Malnev; Igor Bakhovtsev; Gennady Zinoviev (Известия Томского политехнического университета: Инжиниринг георесурсов, 2019)
The review deals with single and three-phase multilevel current source inverters for wind power stations. The review is mainly based on the foreign press. The introduction gives brief justification of significance of using multilevel inverters in wind power stations and comparison of autonomous voltage and current inverters. The accomplishments of current source inverter and its use have been listed. The single-phase versions are considered further. This type of converters is characterized by noncomplex topology (as a rule) and easy studying of forming levels of output current. The base topology is determined for them. For some topologies in comparison with the base one the comparative characteristics are considered for a number of power switches and control systems. Special attention is given to topologies with reduced number of power switches. In addition, the focus is on single-phase multilevel current source inverters, based on no-isolated switches. The features of their management, strengths and weaknesses are considered. The base topology is determined for three-phase multilevel current source inverters. Two three-phase circuit transfer methods using duality principles of current source and voltage source inverters are described. Then some topologies, which had been derived using these principles, are described as well. The paper refers to the problem of the current balance in some cascades of multilevel current source inverters and to the methods of it implementation. This problem is similar to the problem of voltage balance in the multilevel voltage source inverters. The three-phase topologies, which had been acquired from several one-phase cells, are described. It is important for high powerful converters. The paper considers a new class of multilevel current source inverters topologies, which is named a quasi-multi-zone topology. The authors describe its characteristics and advantages. For each topology, described in the paper, the brief descriptions of control algorithms is given. At the end of the article by the results of the prepared review the authors propose the classification of different topologies of multilevel current source inverters by several criteria.